The prevalence and multilevel analysis of minimum dietary diversity intake and its determinants among 6-23 months old infants in The Gambia: further analysis of the Gambian demographic and health survey data - Bewuketu Terefe; Mahlet Moges Jembere; Nega Tezera Assimamaw (BMC, 2023)
Abstract Background Poor infant and young child feeding (IYCF) practices are a significant issue both globally and in developing nations, and they have a significant role in undernutrition, healthy growth, and development, particularly in the first 2 years of life. Improving children's general health and wellbeing requires recognizing and decreasing preventable drivers of malnutrition. Hence, this study aimed to assess the prevalence and possible determinants of minimum dietary diversity among 6-23 months old babies in the Gambia. Methods Data from the 2019-2020 Gambia demographic and health survey were used. The study included a total of 2100 weighted 6-23 months old children. To identify characteristics significantly linked with minimum dietary diversity among infants, a multilevel fixed-effect analysis approach was used. After adjusting other confounding variables, variables with a p value of 0.25 were incorporated into a multivariable multilevel regression analysis to determine associated variables. An adjusted odds ratio with a 95% confidence interval was then applied. Results Only 22.22% (95% CI 18.55, 21.99) of infants had received the minimum dietary diversity. Mothers, who had mass media exposure (aOR = 2.71, CI = (1.02, 6.21), wealthier (aOR = 1.70, CI = 1.02, 2.85), child age of (aOR = 4.14, CI = 2.98, 5.76), and (aOR = 4.97, CI = 3.54, 6.98), have shown a positive statistical association with the outcome variable, respectively. Regarding regions mothers who came from Kanifing (aOR = 0.49, CI = 0.25, 0.94), Janjanbureh (aOR = 0.38, CI = 0.18, 0.82), and Basse (aOR = 0.51, CI = 0.26, 0.99) had showed less likelihood odds to provide the minimum dietary diversity (MDD) for their babies compared to Banjul local government area, respectively. Conclusion The World Health Organization dietary evaluation tool suggests that the MDD value be extremely low, even though it might be slightly higher than the numbers for some nations. The country may need to take drastic measures to tackle child malnutrition.